2024
DOI: 10.3389/fphar.2023.1281002
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Effects of Bushen Daozhuo Granule on Chronic Non-bacterial Prostatitis

Dalin Sun,
Dong Xing,
Dandan Wang
et al.

Abstract: Background: Chronic non-bacterial prostatitis (CNP), one of the most common chronic diseases in urology, leads to pain in the prostate and dysuria, critically affecting the physical or mental health of patients. However, there are no standard treatment approaches for the treatment of CNP in the clinic. Although the clinical application of Bushen Daozhuo granule (BSDZG) offers hope to CNP patients in China, the mechanisms of BSDZG in treating CNP are still not entirely clear. Hence, we aimed to investigate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 47 publications
0
1
0
Order By: Relevance
“…Song et al found that the apoptosis process of RWPE-1 cells was significantly inhibited by LPS, 36 while Sun et al reported that LPS stimulation promoted the apoptosis of RWPE-1 cells. 42 Similarly, the changes in the apoptosis process were also inconsistent with EAP mice model in previous literature. 41 , 43 Our previous review has discussed such inconsistencies.…”
Section: Discussionmentioning
confidence: 87%
“…Song et al found that the apoptosis process of RWPE-1 cells was significantly inhibited by LPS, 36 while Sun et al reported that LPS stimulation promoted the apoptosis of RWPE-1 cells. 42 Similarly, the changes in the apoptosis process were also inconsistent with EAP mice model in previous literature. 41 , 43 Our previous review has discussed such inconsistencies.…”
Section: Discussionmentioning
confidence: 87%
“…These factors were assigned to two categories: infectious and noninfectious. 1,2 It was proposed by the World Health Organization that prostatitis can be divided into four main types based on its distinct etiology and disease course; chronic prostatitis has attracted increased amounts of attention. 3 There are two types of chronic prostatitis: one is caused by pathogens, such as Escherichia coli and Corynebacterium spp., and the other is related to intricate factors.…”
Section: Introductionmentioning
confidence: 99%